Pengaruh Promosi terhadap Keputusan Menginap Konsumen pada Hotel Bubu Suite Ubud dengan Dimoderasi oleh E-Commerce - Putra, I Wayan Gede Andika (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
A purchasing decision is a person’s attitude to buy or use a product or service that they believe in and suits their needs. This also applies to the sustainability of the tourism industry, purchasing decisions can be in the form of consumer stay decisions. The aim of this research is to determine the effect of promotions on consumers’ decision to stay at the Bubu Suite Hotel, Ubud, moderated by e-commerce. The population in this research is all consumers at the Bubu Suite Hotel Ubud with a sample of 100 consumers. Data collection was carried out using observation, interviews, documentation, literature study methods. The data analysis method used is the Simple Linear Regression method and Moderated Regression analysis (MRA). The instrument test was carried out by testing validity and reliability using SPSS software. The results of the analysis show that promotions have a positive and significant effect on consumers’ overnight decisions, E-commerce as a moderating variable has a negative and significant effect. Thus, the E-commerce variable weakens the influence of promotions on consumers’ overnight decisions.